Comparative study of effect of clonidine with lignocaine and lignocaine alone infiltration in middle ear surgeries - Manjunatha Chandrashekar; S.N. Rajesh; K.J. Vedhashree; Prakash Handi; Sunil Khyadi (Al Ameen Journal of Medical Sciences)
Background: Middle ear surgeries are performed under either local or general anaesthesia. Many advantages have been reported with the local anaesthetic techniques. Objectives: To compare the effectiveness of clonidine with lignocaine and lignocaine alone infiltration for middle ear surgeries with respect to duration of analgesia, pain score & surgeon’s satisfaction. Methodology: 66 adult patients undergoing elective middle ear surgeries were divided into two groups, study group A (n=33) and control group B (n=33). 15ml of local anaesthesia infiltrated at posterior auricular area and between tragus and helix using 2% lignocaine with 1 in 200000 dilution of adrenaline with 30mcg of clonidine hydrochloride for study group A and 15ml of 2% lignocaine with 1 in 200000 dilution of adrenaline with 0.2ml normal saline given for control group B by the surgeon, after confirming successful blockade, procedure started. Patients were asked to rate intraoperative pain using visual analogue scale consisting of scoring from 1 to 10. Surgeon satisfaction scores were assessed using Likert scale consisting of scoring from 1 to 7. Results: Demographic data were comparable in both the groups. Duration of analgesia was significantly higher in group A compared to group B. The surgeon satisfaction was better in group A than Group B. SBP and DBP found significantly higher in group B compared to group A. Conclusion: Duration of analgesia and surgeon satisfaction were better in clonidine as adjuvant compared with lignocaine with adrenaline alone infiltration, with well-maintained haemodynamic.